Synthesis, biological evaluation and molecular docking studies of novel benzimidazole derivatives. (February 2018) - Singh, Gagandeep; Singh, Amanjot; Verma, Raman K.; Mall, Rajiv; Azeem, Uzma
Graphical abstract: Highlights: Novel synthesized compounds were found to have inhibitory potential against α -amylase and α -glucosidase. Docking Studies were carried out in the active site of the α -glucosidase protein (PDB code: 3TOP) using SYBYL 7.3 software. Docking results also supported biological activity results. The structure of the novel synthesized compounds was confirmed through the spectral studies (LC-MS, 1 H-NMR, 13 C-NMR, FT-IR). Abstract: A novel series of N -substituted-benzimidazolyl linked para substituted benzylidene based molecules containing three pharmacologically potent hydrogen bonding parts namely; 2, 4-thiazolidinedione (TZD: a 2, 4-dicarbonyl), diethyl malonate (DEM: a 1, 3-diester and an isooxazolidinedione analog) and methyl acetoacetate (MAA: a β -ketoester) (6a–11b ) were synthesized and evaluated for in vitro α -glucosidase inhibition. The structure of the novel synthesized compounds was confirmed through the spectral studies (LC–MS, 1 H NMR, 13 C NMR, FT-IR). Comparative evaluation of these compounds revealed that the compound9b showed maximum inhibitory potential against α-amylase and α-glucosidase giving an IC50 value of 0.54 ± 0.01 μM. Furthermore, binding affinities in terms of G score values and hydrogen bond interactions between all the synthesized compounds and the AA residues in the active site of the protein (PDB code:3TOP ) to that of Acarbose (standard drug) were explored with the help of molecular docking studies. Compound9b was considered as promising candidate of this series.